Clear Aligners versus 2x4 mechanics comparison in the mixed dentition: a randomized clinical trial - Silva, Vinicius Augustus Merino da (2021)
Introduction: The aim of this study was to compare the efficacy and efficiency of clear aligners and 2x4 fixed appliances for solving maxillary incisor position irregularities in the mixed dentition. Methods: The sample was composed by 27 patients from 7 to 11 years of age that were randomly allocated into two treatment groups: Group CA 14 patients treated with invisible aligners; and Group FA 13 patients treated partial fixed appliances in a 2x4 mechanics. Digital models were acquired before treatment (T1) and after the appliance removal (T2). Primary outcomes were: Little irregularity index and treatment time. Secondary outcomes were arch width, perimeter and length, arch size and shape, incisors levelling, plaque and ICDAS index. Intergroup comparisons were evaluated using Student t-test and Wilcoxon test with Holm-Bonferroni correction (p < 0.05). Results: The final sample comprised 14 patients (6 female, 8 male) with a mean age of 9.3 years (SD=1.0) in Group CA and 13 patients (9 female, 4 male) with a mean age of 9.6 years (SD=0.8) in Group FA. No intergroup differences were observed for changes in the incisor irregularity index. Treatment time was similar in both groups. Arch width, length, size and shape changes presented similar changes during treatment. Plaque and ICDAS index showed no differences between groups. Conclusion: Clear aligners and 2x4 mechanics presented similar efficacy and efficiency for maxillary incisor positional corrections in the mixed dentition.